FUZZY SUGENO- BIOMEKANIKA-NIOSH-NBM: PENILAIAN RISIKO AKTIVITAS PENYARINGAN BUBUR KEDELAI - Johan Alfian Pradana; Ilham Fauzul Fahmi; Erwin Putra Setya Indiarto; Sindy Nindia Maretha Haristanti (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
The purpose of this study was for risk assessment of soybean pulp filtration activities using Fuzzy Sugeno, NBM, Biomechanics, and NIOSH. Design this research with fuzzy integration – ergonomics. Research methods with observation stages and documentation of working postures, filling NBM questionnaires, assessing Fcompression and Fshear, designing fuzzy sugeno to assess job risks. The findings in this study were a 35% risk of fuzzy sugeno approaching pain. NBM pain points ≥ 80% with biomechanics value declared Fcompression and Fshear meet not at risk. An average Lifting Index assessment of 1.8 kg may be at risk for soy porridge filtering activities. Overall, soy porridge filtration activities still have risks. Therefore, it needs to be reviewed further. Improvements in the work environment and work facilities can also support in reducing the risk of muscle injury while working